ANALISIS TEORI MAX WEBER PADA MOTIVASI PESERTA DIDIK MEMILIH MENGAJI DI MADRASAH DINIYAH MAZROATUL ILMI - Lathifatus Saidah (Ibtidaiyyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to determine the motivation of students to choose the Koran at madrasah diniyah Mazroatul Ilmi. The subjects in this study were all 6th grade students of madrasah diniyah Mazroatul Ilmi. The method used by the researcher is descriptive qualitative method. The results of the study indicate that the motivation of students to choose the Koran at Madrasah diniyah Mazroatul Ilmi varies. If classified based on social action according to Max Weber, among others, 50% of students fall into the category of goal rational social action, 25% of students fall into the category of value rational social action, and 25% of students fall into the category of traditional social action ABSTRAK Penelitian ini bertujuan untuk mengetahui motivasi peserta didik memilih mengaji di madrasah diniyah Mazroatul Ilmi. Subjek dalam penelitian ini adalah seluruh siswa kelas 6 madrasah diniyah Mazroatul Ilmi. Metode yang digunakan peneliti adalah metode kualitatif deskriptif. Dari hasil penelitian menunjukkan bahwa motivasi siswa memilih mengaji di Madrasah Diniyah Mazroatul Ilmi beragam. Jika diklasifikasikan berdasarkan tindakan sosial menurut Max Weber antara lain 50% peserta didik masuk dalam kategori goal rational social action, 25% peserta didik masuk dalam kategori value rational social action, dan 25% peserta didik masuk dalam kategori traditional social action.